Development and validation of the Greek version of weight pressures in sport-females questionnaire - Kontele, I.; Vassilakou, T.; Psychountaki, M.; Reel, J. J.; Donti, O. (Journal of Clinical Sport Psychology, 2023)
Weight Pressures in Sport—Females (WPS-F) questionnaire measures sportrelated pressures that female athletes experience regarding body weight, shape, size, and appearance. In order to examine the psychometric properties of the Greek version of the inventory, two different studies were conducted. In the first study, using a sample (n = 225) of female Greek athletes aged 12-20 years, exploratory factor analysis produced two factors (Factor 1: Pressures From Coaches and Sports About Weight and Factor 2: Pressures Regarding Appearance and Performance) and supported the original factor structure. In the second study, using a different sample (n = 318) of female Greek athletes aged 11- 18 years, confirmatory factor analysis provided support for the two-factor structure. Weight Pressures in Sport—Females questionnaire was demonstrated to be a valid and reliable instrument for Greek female athletic populations. Future studies should further test the factorial structure in younger and older athletes and in larger samples.